The Role of Graphic Novels in Promoting Literacy - Feichal Abdou Moumouni (20634815) (2024)
This presentation will explore the significant role graphic novels play in promoting literacy across diverse age groups and learning environments. Graphic novels combine visual storytelling with text to create an engaging and dynamic learning experience, making them an effective tool in fostering reading skills. By addressing the needs of reluctant readers and those with varying learning styles, graphic novels encourage both visual and textual literacy. The presentation will highlight their educational value, from enhancing comprehension and critical thinking to promoting cultural understanding and language acquisition. Additionally, the discussion will cover how graphic novels can be integrated into classroom settings, libraries, and digital platforms to support multimodal learning and reading engagement. Other Information License: http://creativecommons.org/licenses/by/4.0/